Podgotovka velosipedistov-sosseinikov vysokoi kvalifikacii v uslovijah elitnogo professional'nogo kalendarja sorevnovanii - Erdakov, S. V.; Zaharov, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to reveal the peculiarities of elite cyclists training in the conditions of the professional racing competitions calendar. The obtained data allows to state that in year cycle of elite racer competing in the conditions of the professional calendar must be in accordance with the unique purpose problem of the successful participation in competitions. It is necessary to realize the selective approach, supposing the accurate distribution of personal training programmes for every racer according their orientation to the certain professional rounds or competitions.